Application of a mental imagery protocol for the promotion of implicit learning in university students - Mora-Benambourg, José Manuel (2024)
Objective. The improvement of cognitive skills has become an issue of particular interest nowadays. It is still being determined if techniques like mental imagery (MI) could generate cognitive enhancement via modulation of neural brain activity. This study aimed to provide information on the impact of mental imagery on implicit motor learning. Method. To test this hypothesis, an MI protocol was applied to an experimental group before performing an implicit learning (IL) task, while a control group received a sham feedback protocol. In addition, to have empirical evidence of cortical activation during MI, we made an electroencephalographic (EEG) record of motor cortex activity during baseline and during the task associated with IL. Results. The ANCOVA models all together show how the MI protocol does impact the IL process, but not as clearly as expected.